(untitled) (CIPEEX, 2022)
ACCORDING TO THE CF/88 IN ITS ARTICLE 205, EVERYONE HAS THE RIGHT TO EDUCATION, AND ITS PROMOTION IS A DUTY OF THE STATE AND THE FAMILY. HOWEVER, DUE TO THE CURRENT PANDEMIC SITUATION, EDUCATION HAS GAINED A NEW FORMAT, REMOTE CLASSES. IN THIS SENSE, THE PRESENT WORK HAS AS ITS GENERAL OBJECTIVE TO ANALYZE WHETHER THE CHILDREN OF THE INSTITUTION CMEI PADRE JOS, SETOR ARACY AMARAL IN THE CITY OF SENADOR CANEDO - GO HAVE ACCESS TO REMOTE CLASSES. TO REACH THE EXPECTED RESULTS, THE FOLLOWING SPECIFIC OBJECTIVES WERE FORMULATED: A) TO GIVE VOICE TO THOSE RESPONSIBLE FOR THE CHILDREN BELONGING TO THE INSTITUTION; B) TO MAKE A LEGAL ANALYSIS ABOUT THE ACCESS TO EDUCATION; C) TO ANALYZE IF THE CHILDREN OF THE INSTITUTION HAVE ACCESS TO REMOTE MEANS FOR NON PRESENTIAL CLASSES. TO THIS END, THE FOLLOWING QUESTION WAS DEFINED AS THE GUIDING PROBLEM OF THIS STUDY: DO THE CHILDREN OF THE PADRE JOS CMEI HAVE FULL ACCESS TO REMOTE MEANS TO PARTICIPATE IN NON PRESENTIAL CLASSES? THE METHODOLOGICAL CONSTRUCT USED TO OBTAIN THE DATA FOR THIS RESEARCH CONSISTED OF BIBLIOGRAPHIC, DOCUMENTAL, QUALITATIVE, FIELD, EXPLORATORY, AND EXPLANATORY RESEARCH. THE PRESENT STUDY HAS A HIGH DEGREE OF IMPORTANCE IN THE LEGAL, SCIENTIFIC AND SOCIAL FIELDS, AS IT AIMS TO ADDRESS THE ISSUE OF INCLUSION IN EARLY CHILDHOOD EDUCATION AT THE CMEI PADRE JOS. THUS, IT IS IMPORTANT TO ADDRESS THE PROPOSED THEME, SINCE THE RESULTS OBTAINED POINT TO THE LACK OF ACCESSIBILITY OF AVENIDA TANCREDO NEVES, VIOLATING THE FUNDAMENTAL RIGHT TO ACCESSIBILITY PROVIDED IN THE FEDERAL CONSTITUTION.&NBSP;